Species composition and relative abundance of fish larvae found in Taklong Island National Marijne RTeserve (TINMAR). - Delola, Afredo P.
The study examined the distribution of major groups of fish larvae in the area within the barangay of La Paz and San Roque in the municipality of Nueva Valencia, Guimaras which has a total area of 1,143.455 hectares designated as the Taklong Island National Marine Reserve (TINMAR). The obejective of the study were: 1) To determine the species composition and relative abundance of the major groups of fish larvae in the area, and 2) To examine the temporal variation in abundance, 3) To know how many larval types and which are the most abundant and when, 4) To know when is fish larval abundance highest, which months more similar to the other.